Bridging the gap: addressing real-life challenges to the implementation of DTG/3TC in treatment-naive people living with HIV - Giacomelli, Andrea; Baldin, Gianmaria; Bono, Valeria; Ciccullo, Arturo; Mazzitelli, Maria; Poliseno, Mariacristina; Ridolfi, Marco; Sozio, Federica; Teti, Elisabetta; Marchetti, Giulia (Frontiers in Virology, 2026)
Dolutegravir/lamivudine (DTG/3TC), used as a two-drug regimen (2DR), has demonstrated non-inferiority to traditional three-drug regimens (3DRs) in treatment-naive people with HIV (PWH), with sustained virological efficacy, favorable tolerability, and a good safety profile. However, its implementation in routine clinical practice raises several questions, particularly in populations underrepresented in registration trials. This review critically appraises current evidence supporting DTG/3TC as first-line antiretroviral therapy, drawing from randomized clinical trials and real-world studies. Available data indicate that DTG/3TC maintains high virological suppression rates even in individuals with high baseline viral load (>500,000 copies/mL), with no emergent resistance. Evidence from test-and-treat settings suggests comparable efficacy to triple therapy, provided that hepatitis B coinfection and transmitted resistance are adequately excluded. Preliminary data in late presenters and those with advanced disease support its effectiveness, although confirmatory trials are warranted. Beyond viro-immunological outcomes, DTG/3TC appears equivalent to triple regimens in reducing viral reservoirs, immune activation, and systemic inflammation. Evidence in women living with HIV, including during pregnancy, remains limited but reassuring, with no major safety concerns identified. Overall, the body of clinical and real-world evidence supports DTG/3TC as a simplified and durable first-line regimen for most treatment-naive PWH. Ongoing research should further define its role in acute infection, advanced HIV disease, and specific subpopulations such as women and individuals from regions with high prevalence of non-B subtypes.